Aortic arch surgery at 32°C: mild hypothermia and unilateral antegrade cerebral perfusion. (12th January 2021) - Jabagi, Habib; Juanda, Nadzir; Nantsios, Alex; Boodhwani, Munir
Abstract:  : OBJECTIVES: With development of antegrade cerebral perfusion, the necessity of deep hypothermic circulatory arrest (CA) in aortic arch surgery has been called into question. To minimize the adverse effects of hypothermia, surgeons now perform these procedures closer to normothermia. This study examined postoperative outcomes of hemiarch replacement patients using unilateral selective antegrade cerebral perfusion and mild hypothermic CA. METHODS: Single-centre retrospective review of 66 patients undergoing hemiarch replacement with mild hypothermic CA (32°C) and unilateral selective antegrade cerebral perfusion between 2011 and 2018. Antegrade cerebral perfusion was delivered using right axillary artery cannulation. Postoperative data included death, neurological dysfunction, acute kidney injury and renal failure requiring new dialysis. Additional intraoperative metabolic data and blood transfusions were obtained. RESULTS: Eighty-six percent of patients underwent elective surgery. Mean age was 67 ± 3 years. Lowest mean core body temperature was 32 ± 2°C. Average CA was 17 ± 5 min. No intraoperative or 30-day mortality occurred. Survival was 97% at 1 year, 91% at 3 years and 88% at 5 years. Permanent and temporary neurological dysfunction occurred in 1 (2%) and 2 (3%) patients, respectively. Only 3 (5%) patients suffered postoperative stage 3 acute kidney injury requiring new dialysis. Intraoperative transfusions occurred in 44% of patients and no major metabolic derangements were observed. CONCLUSIONS: In patients undergoing hemiarch surgery, mild hypothermia (32°C) with unilateral selective antegrade cerebral perfusion via right axillary cannulation is associated with low mortality and morbidity, offering adequate neurological and renal protection. These findings require validation in larger, prospective clinical trials.